Clearing the cervical spine in patients with distracting injuries: An AAST multi-institutional trial. Issue 1 (January 2019) - Khan, Abid D.; Liebscher, Sean C.; Reiser, Hannah C.; Schroeppel, Thomas J.; Anstadt, Michael J.; Bosarge, Patrick L.; Carroll, Shannon L.; Quick, Jacob A.; Barnes, Stephen L.; Sobrino, Justin; Murry, Jason; Morin, Nicholas; et al.
Abstract : BACKGROUND: Single institution studies have shown that clinical examination of the cervical spine (c-spine) is sensitive for clearance of the c-spine in blunt trauma patients with distracting injuries. Despite an unclear definition, most trauma centers still adhere to the notion that distracting injuries adversely affect the sensitivity of c-spine clinical examination. A prospective AAST multi-institutional trial was performed to assess the sensitivity of clinical examination screening of the c-spine in awake and alert blunt trauma patients with distracting injuries. METHODS: During the 42-month study period, blunt trauma patients 18 years and older were prospectively evaluated with a standard c-spine examination protocol at 8 Level 1 trauma centers. Clinical examination was performed regardless of the presence of distracting injuries. Patients without complaints of neck pain, tenderness or pain on range of motion were considered to have a negative c-spine clinical examination. All patients with positive or negative c-spine clinical examination underwent computed tomography (CT) scan of the entire c-spine. Clinical examination findings were documented prior to the CT scan. RESULTS: During the study period, 2929 patients were entered. At least one distracting injury was diagnosed in 70% of the patients. A c-spine injury was found on CT scan in 7.6% of the patients. There was no difference in the rate of missed injury when comparing patients with a distracting injury to those without a distracting injury (10.4% vs. 12.6%, p = 0.601). Only one injury missed by clinical examination underwent surgical intervention and none had a neurological complication. CONCLUSIONS: Negative clinical examination may be sufficient to clear the cervical spine in awake and alert blunt trauma patients, even in the presence of a distracting injury. These findings suggest a potential source for improvement in resource utilization. LEVEL OF EVIDENCE: Therapeutic/care management, level IV.